PENGARUH PENGETAHUAN KEWIRAUSAHAAN DAN KEUNGGULAN BERSAING TERHADAP KEBERHASILAN USAHA DAGANG DI KELURAHAN PASAR TELUKDALAM - Louis Jeffry Sihura (Universitas Nias Raya, 2026)
The purpose of this study was to determine the effect of entrepreneurial knowledge and competitive advantage on the success of trading businesses in Telukdalam City. The type of research used is quantitative research. The type of data used in this study is the type of primary data, namely data obtained directly from respondents. The data source used in this study is from trading business actors by using a questionnaire with 42 respondents. The data collection technique is a questionnaire by giving a list of statements to respondents to fill out. The data analysis method used is simple regression analysis. Based on the results of hypothesis testing research with a value of t_hitung = 3.025> t_table = 1.682 on entrepreneurial knowledge and t_hitung = 2.981> t_table = 1.682 on competitive advantage, meaning that there is an influence of entrepreneurial knowledge and competitive advantage on the success of trading businesses in Telukdalam City. The suggestions for this study are (1) To increase business success in trading businesses in the city of Telukdalam, you should have entrepreneurial knowledge that can optimize a business on the road.